The Influence of Transformational Leadership and Knowledge Management on Organizational Performance at Coffee Shop in Bekasi City - Musa’ad, Miskia; Richo Rianto, Muhammad; Eri Bukhari (Draf Solusi Indonesia, 2023)
Transformational leadership and knowledge management on organizational performance in coffee shops. This study aims to determine how the influence of transformational leadership and knowledge management on organizational performance at coffee shops in North Bekasi. In this study, researchers used a quantitative approach with the Smart PLS method which is useful for analyzing the influence of transformational leadership and knowledge management on organizational performance at coffee shops in North Bekasi city using 46 respondents who were randomly distributed through questionnaires to the owner of each coffee shop.